Acute Phase Proteins: Implications for Animal Disease Prevention and Management - Akamsha Garg; Lealpana Shay; Amitler Singh; Vimal Kumar (The Indian Veterinary Journal, 2026)
Acute phase proteins (APPs) are biomarkers that are essential for comprehending the dynamic interactions that occur within biological systems in response to infections, physiological processes, or therapeutic interventions. These proteins play a crucial role in illustrating the complex interactions that occur between cytokines, innate immune responses, and changes in serum concentrations during the acute-phase response. Although APPs are widely used in human medicine, their application in Veterinary Sciences is limited. Current research has identified about 40 distinct APPs in different species. The role of APPs in food safety, drug development, and general animal welfare, beyond disease management, calls for identifying APPs in animals. A comprehensive strategy combining biomarker measurements with other diagnostic tools for improved clinical precision is required. The review explores the complex role that APPs, especially C-reactive protein, serum amyloid A, haptoglobin, and alpha-1 acid glycoprotein, play in animal health, emphasizing their importance in prognosis, diagnosis, and therapeutic monitoring and highlights the importance of finding new biomarkers for proactive healthcare management.